A case that illustrates the challenges of managing pregnant patients with antithrombin deficiency: More questions than answers. Issue 157 (September 2017) - Skeith, Leslie; Aw, Andrew; Hews-Girard, Julia; Rydz, Natalia
Abstract: Using an illustrative case of a patient with antithrombin (AT) deficiency who developed a recurrent venous thromboembolism (VTE) in pregnancy despite therapeutic low-molecular-weight heparin (LMWH), we highlight what is known in the literature and address areas of controversy through a series of questions around the case. The questions we address include the role of anti-Xa monitoring for patients with past VTE on antepartum LMWH, what treatment regimen is recommended for pregnant patients who develop a recurrent VTE while on therapeutic anticoagulation, the role of antepartum AT concentrate prophylaxis, and the management of labor/delivery, epidural anesthesia and postpartum anticoagulation. We also describe practical considerations for use of AT concentrate, including teaching our patient to self-infuse AT concentrate at home with support of a hemophilia treatment center (HTC), and the direct and indirect costs of AT concentrate for secondary prophylaxis. Highlights: Management of pregnant patients with antithrombin (AT) deficiency is challenging. There is little evidence to guide practice for use of AT concentrate in pregnancy. The cost-effectiveness of prophylaxis with AT concentrate in pregnancy is unknown. Teaching patients to self-infuse AT concentrate during pregnancy is possible.